The Expansion of Bank Credit: An Alternative Approach - Shearer, Ronald A. (Quarterly Journal of Economics, 1963)
I. Credit expansion versus monetary expansion in the theory of monetary policy, 486. — II. The balance sheet identity, 489. — III. The credit control identity, 491. — IV. A static credit expansion multiplier, 492. — V. A priori magnitude of the multiplier, 494. — VI. Variability of the security-asset ratio, 496. — VII. A multiplier incorporating portfolio reactions, 496. — VIII. Tentative empirical verification, 498.